Pengaruh Konten Vlog Akun Youtube Tasya Farasya Terhadap Minat Beli Subscribers - Dian Pertiwi; Effiati Juliana Hasibuan; Ara Auza (Universitas Medan Area, 2022)
This study aims to determine and analyze the influence given by beauty vloggers on buying interest a skin care product through social media Youtube. The vlog content uploaded by Tasya Farasya is used as a medium to share information and experiences from the use of a care and beauty product. Tasya Farasya's knowledge and experience can be a source of advice and influence on purchases. The method used is a quantitative study using the Slovin formula, and obtained a sample of 100 respondents. The analysis was carried out using the Product Moment Correlation Test and the Determination Test with the SPSS version 21. The results of the study stated that there was an influence between Tasya Farasya's Youtube account on buying interest a skin care products. The conclusion of the study proves that the presence of beauty vloggers on Youtube social media is very beneficial for companies to carry out marketing activities. The credibility and popularity of a beauty vlogger will attract followers to make purchases of the products reviewed.